Sustainable Development Disciplines for Humanity (Springer Nature, 2022)
This Open Access book provides eight problem solving lectures for sustainable development for people, peace, and partnerships. Those are three of the five keywords for the Sustainable Development Goals (SDGs): people, the planet, prosperity, peace, and partnerships or “the 5Ps”. Each of these lectures is classified into one of the keywords for SDGs and based on the history of social thought, human development, law, education, sociology, and peace studies. Further, each lecture delineates the essence of each discipline when it is practically applied to development studies. This book, Sustainable Development Disciplines for Humanity, along with its sister volume related to the planet and prosperity, Society, will be useful in studying development. Interdisciplinary research is necessary to achieve the SDGs advocated by the United Nations. Hence, it is essential to learn the basics of individual disciplines, as they each offer ample knowledge fostering problem solving through the accumulation of existing research. This and its sister volume are the first comprehensive textbooks summarizing the essence of each necessary discipline to approach development studies from an interdisciplinary perspective. In developing countries, this book will provide access to development research for readers aiming to further develop their own nations. Moreover, in developed countries, the book will provide access to problem-solving research for readers seeking holistic solutions to complex social problems.